PENGARUH STATUS SOSIAL EKONOMI ORANG TUA DAN LINGKUNGAN SEKOLAH TERHADAP MOTIVASI MELANJUTKAN KE PERGURUAN TINGGI PADA SISWA KELAS XII SMA NEGERI 3 PANYABUNGAN - Nurul Fachrissa Lubis; Salman M. Noer; Reni Respita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ekasakti, 2024)
The purpose of this study was to describe and analyze the influence of socio-economic status of people and the school environment on students' motivation to continue higher education in class XII SMA N 3 Panyabunagn. The population which is also the research is 158 students of class XII. The variables studied were parents' socioeconomic status and school environment as independent variables and motivation to continue tertiary education as the dependent variable. Data were obtained from questionnaires and analyzed using regression with the help of the SPSS program with a significance level of 0.05. The results of this study show that parents' socio-economic status has a positive and insignificant effect on motivation to continue higher education, as evidenced by the results with t = 1.367 and p = 0.174 < 0.05. The school environment has a positive and insignificant effect on motivation to continue to college, as evidenced by tcount = 1.1959 and p = 0.053 < 0.05. The socio-economic status of parents and the school environment simultaneously influence the motivation to continue to higher education. proven from Fcount = 3.978 and p value = 0.021.